2000
DOI: 10.1002/(sici)1097-0142(20000225)90:1<55::aid-cncr8>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic differential diagnosis among reactive mesothelial cells, malignant mesothelioma, and adenocarcinoma

Abstract: BACKGROUND The differential diagnosis between reactive mesothelial cells (RMs), malignant mesotheliomas (MMs), and adenocarcinomas (ACs) is often difficult in cytologic specimens, and the utility of various immunohistochemical markers have been explored. Because recent immunohistologic studies have suggested that E‐cadherin (E‐cad) and calretinin (Cal) may be useful markers for epithelial and mesothelial differentiations, respectively, the authors investigated their utility in cytologic diagnosis. METHODS In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 18 publications
2
78
0
Order By: Relevance
“…In some immunocytochemical studies, CALB2 was positive in most of benign effusions (94-100%; refs. 12,20). It is difficult to compare these results with ours, because the expression of CALB2 was detected at two different levels (protein or mRNA).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In some immunocytochemical studies, CALB2 was positive in most of benign effusions (94-100%; refs. 12,20). It is difficult to compare these results with ours, because the expression of CALB2 was detected at two different levels (protein or mRNA).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, if Ep-CAM seems to be of limited interest to distinguish carcinoma from mesothelioma effusions, it is a valuable molecular marker for the detection of tumor cells in serous effusions. CDH1, an epithelial-specific adhesion molecule, has been proven to reliably distinguish carcinoma cells from benign reactive mesothelial cells, but not from mesothelioma cells, in serous effusions by immunocytology (12,20,33). We also found that CDH1 was specifically expressed in malignant epithelial and nonepithelial serous effusions, but it was not very sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…A few potentially useful markers, such as E-cadherin and N-cadherin, were omitted because of conflicting reports about their performance in distinguishing mesothelioma from AdCA. 57,[69][70][71][72] A third strength of our study was the detailed statistical analysis, which distinguishes this study from most previous studies in this area. Not only were all antibodies evaluated by univariate analysis to determine their abilities to distinguish MEM from all AdCA ( Table 2, column 2), but the relative utility of each antibody was quantified by ROC curve analysis ( Table 2, column 3), the relevant sensitivities and specificities were calculated for each MEM-and AdCA-associated antibody (Table 3), and LR was applied to determine the optimal combination of antibodies for distinguishing MEM from AdCA.…”
Section: Discussionmentioning
confidence: 99%
“…33 Another assessment by Kitazume et al demonstrated that reactive mesothelial cells typically lack E-cadherin whereas virtually all malignant mesotheliomas express that marker along with 85% of adenocarcinomas. 34 Davidson et al also showed that desmin was present in 84% of reactive mesothelial cells, as compared with 2% of carcinomas and 8% of mesotheliomas. 35 Simulants of Small Cell Carcinoma (Table III) We would be remiss if we failed to mention the false-positive diagnosis of small cell carcinoma in patients with reserve cell bronchial hyperplasia, follicular bronchitis, or non-Hodgkin lymphoma.…”
Section: False-positive Pleural Cytologymentioning
confidence: 91%